Is AI Cost-Effective for Small Clinics? An Academic Analysis of ROI in Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Is AI Cost-Effective for Small Clinics? An Academic Analysis of ROI in Digital Health The integration of Artificial Intelligence (AI) into healthcare is...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Medical AI